Exploring the Ambiguous Status of Coagulase-Negative Staphylococci in the Biosafety of Fermented Meats: The Case of Antibacterial Activity Versus Biogenic Amine Formation - Van der Veken, David (Microorganisms, 2020)
A total of 332 staphylococcal strains, mainly isolated from meat, were screened for antibacterial activity. Eighteen strains exhibited antibacterial activity towards species within the same genus. These antibacterial strains were further screened against Clostridium botulinum, to assess their potential as anticlostridial starter cultures for the development of fermented meat products without added nitrate or nitrite. Only Staphylococcus sciuri IMDO-S72 had the ability to inhibit all clostridial strains tested, whilst displaying additional activity against Bacillus cereus, Listeria monocytogenes and Staphylococcus aureus. Apart from their potential as bioprotective cultures, the staphylococcal collection was also screened for biogenic amine production, as these compounds may compromise food quality. To this end, ultra-high-performance liquid chromatography coupled to tandem mass spectrometry (UPLC-MS/MS) was applied. A low incidence of biogenic amine production was found, with tyramine and β-phenylethylamine being the most prevalent ones. Concentrations remained relatively low (< 52 mg/L) after a prolonged incubation period, posing no or little threat towards food safety. Taken together, S. sciuri IMDO-S72 could serve as an interesting candidate for the bioprotection of fermented meats as it showed promising antibacterial activity as well as absence of biogenic amine production.